2019
DOI: 10.1002/joc.6350
|View full text |Cite
|
Sign up to set email alerts
|

Global characterization of hydrological and meteorological droughts under future climate change: The importance of timescales, vegetation‐CO2feedbacks and changes to distribution functions

Abstract: There is a strong scientific debate on how drought will evolve under future climate change. Climate model outputs project an increase in drought frequency and severity by the end of the 21st century. However, there is a large uncertainty related to the extent of the global land area that will be impacted by enhanced climatological and hydrological droughts. Although climate metrics suggest a likely strong increase in future drought severity, hydrologic metrics do not show a similar signal. In the literature, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 55 publications
4
80
0
Order By: Relevance
“…Irrespective of the wide spectrum of uncertainty introduced in this kind of models when reproducing the temporal variability of soil moisture observations (see Ford & Quiring, 2019;Stillman et al, 2016;Yuan & Quiring, 2017), we stress that the enhanced role of AED on plant dryness under low-precipitation periods would not be well-recorded if we only consider soil moisture but we do not assess the AED influence. Moreover, several studies agree that the projections of soil moisture and SPEI for future scenarios are almost identical (see Feng et al, 2017;Vicente-Serrano et al, 2019;Xu et al, 2019), and even comparable to those suggested by PDSI (Dai et al, 2018).…”
Section: 1029/2020jd033017supporting
confidence: 61%
See 1 more Smart Citation
“…Irrespective of the wide spectrum of uncertainty introduced in this kind of models when reproducing the temporal variability of soil moisture observations (see Ford & Quiring, 2019;Stillman et al, 2016;Yuan & Quiring, 2017), we stress that the enhanced role of AED on plant dryness under low-precipitation periods would not be well-recorded if we only consider soil moisture but we do not assess the AED influence. Moreover, several studies agree that the projections of soil moisture and SPEI for future scenarios are almost identical (see Feng et al, 2017;Vicente-Serrano et al, 2019;Xu et al, 2019), and even comparable to those suggested by PDSI (Dai et al, 2018).…”
Section: 1029/2020jd033017supporting
confidence: 61%
“…There are also important statistical issues that should be carefully considered when interpreting drought changes associated with AED. These concerns are mostly related to how drought metrics are calculated (S. M. Vicente‐Serrano et al, 2019). Overall, the different assumptions about the role of AED in drought severity, as revealed by climate drought metrics, are still questionable and deserve much more attention for better interpretation and understanding of drought severity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies focusing on this topic usually merge both concepts when evaluating future projections (Dai et al, ; Scheff, , ). In areas in which an important decline in water availability is projected, it is difficult to separate both phenomena, since most of the values recorded in the projections would correspond to those located in (or below) the lower tail of the probability distribution in relation to the values recorded over the historical period (Vicente‐Serrano,Domínguez‐Castro, et al, ). Therefore, these values would be very anomalous in relation to the historical period.…”
Section: Co2‐driven Radiative Forcing Versus Co2 Physiological Effectmentioning
confidence: 99%
“…Nevertheless, despite large uncertainties in the climate model projections for future scenarios, it should be always considered that climate models themselves are fully coupled atmosphere–land (and ocean) models, which are internally consistent (yet imperfect) representations of the climate system (Milly & Dunne, ; Y. Yang et al, ). In this light, to ensure the consistency between calculated drought indices and climate model themselves is the key for assessing future drought changes based on climate model projections (Vicente‐Serrano, Domínguez‐Castro, McVicar, et al, ).…”
Section: Co2‐driven Radiative Forcing Versus Co2 Physiological Effectmentioning
confidence: 99%
“…Studies suggest an increase in the intensity and frequency of droughts by the end of the century worldwide due to atmospheric evaporative demand increases, reducing water availability, soil water storage, and agricultural production [15,33,34]. Yet, Santos et al [35] observed a reduction in the water table in the PRB wetlands, downstream of the streamflow gauge station of this study, due to a The most significant meteorological droughts occurred during the hydrological years of 1986/87, 1994/95, 1995/96, 1997/98, 2007/08, and between 2014/15 and 2016/17 in the PRB.…”
Section: Meteorological and Hydrological Droughtsmentioning
confidence: 99%